NOTHING BEATS A FABULOUS POST: THE INFLUENCE OF INSTAGRAM MARKETING FOR VALUE CREATION AND PROMOTION - Jenifer Jenifer; Catharina Badra Nawangpalupi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The study aims to identify the effectiveness of social media marketing, specifically Instagram marketing, for product promotion based on the product and service’s value for MSMEs. Indonesian MSMEs have difficulty to identify its competitive advantages and to promote their product and services’ value to their consumers. Using case studies for local brand restaurants in Bandung, this study explores how social media promotion has helped the restaurants to identify their visual identity and to increase consumer engagement so that they can improve their promotion effectively. This study is a qualitative study that explores factors influencing marketing strategy for value creation and promotion. Using a qualitative study with two case studies, the research shows that social media marketing is an important aspect for small F&B businesses in Bandung. Specifically, Instagram marketing would give small businesses an affordable option and opportunity to boost their brands and enhance their reach through the content. It provides interaction with the audiences and the relationship made with their consumers creates valuable values and intrigues voluntary brand advocation.